2014
DOI: 10.5194/bg-11-147-2014
|View full text |Cite
|
Sign up to set email alerts
|

Distinct bacterial-production–DOC–primary-production relationships and implications for biogenic C cycling in the South China Sea shelf

Abstract: Abstract. Based on two summer spatio-temporal data sets obtained from the northern South China Sea shelf and basin, this study reveals contrasting relationships among bacterial production (BP), dissolved organic (DOC) and primary production (PP) in the transition zone from the neritic to the oceanic regions. Inside the mid-shelf (bottom depth < 100 m), where inorganic nutrient supplies from river discharge and internal waves were potentially abundant, BP, DOC and PP were positively intercorrelated, whereas the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…The latter is based on bacterial uptake of dissolved organic carbon (DOC), which may be provided by primary production or by external sources, such as river discharge. Lai et al (2014) conducted two summer cruises in the northern SCS and found evidence to support the malfunctioning microbial-loop hypothesis proposed by Thingstad et al (1997) that DOC accumulation occurs when bacterial production was low. In contrast to the short DOC turnover time of 37-60 days observed in the inner shelf near the mouth of the Pearl River, it was more than 100 days in the outer shelf and basin region, where the inorganic nutrients were depleted and no correlations were found among bacterial production (BP), DOC and primary production (PP) in the shelf-to-basin transition zone (Fig.…”
Section: Continental Margin Biota and Their Ecological Characteristicsmentioning
confidence: 69%
See 1 more Smart Citation
“…The latter is based on bacterial uptake of dissolved organic carbon (DOC), which may be provided by primary production or by external sources, such as river discharge. Lai et al (2014) conducted two summer cruises in the northern SCS and found evidence to support the malfunctioning microbial-loop hypothesis proposed by Thingstad et al (1997) that DOC accumulation occurs when bacterial production was low. In contrast to the short DOC turnover time of 37-60 days observed in the inner shelf near the mouth of the Pearl River, it was more than 100 days in the outer shelf and basin region, where the inorganic nutrients were depleted and no correlations were found among bacterial production (BP), DOC and primary production (PP) in the shelf-to-basin transition zone (Fig.…”
Section: Continental Margin Biota and Their Ecological Characteristicsmentioning
confidence: 69%
“…The nutrient supply from marine origin is often actuated by intrusion onto the shelf from boundary currents, such as the Kuroshio, which carries a large nutrient load with a subsurface core . In the inner shelf where nutrients are replete, primary production (PP) and bacterial production (BP) are tightly coupled driving a rapid turnover of dissolved organic carbon (DOC), whereas, in the oligotrophic outer shelf, the two are decoupled and DOC tends to accumulate due to low turnover rate (Lai et al, 2014). in the Changjiang plume in summer appeared to have shown a decrease, which is attributed to the enhanced CO 2 uptake by phytoplankton due to the increasing load of riverine nutrients. Subsequent to the phytoplankton bloom, water column respiration led to the elevated pCO 2 in the surface water in autumn.…”
Section: Increasing Atmospheric Co 2 and Changing Carbonate Chemistrymentioning
confidence: 99%
“…While even assuming that the seawater exchange occurred, the chemicals that originated from the Atoll were poor in quality for bacterial growth at the four near-shore stations. Moreover, the total volume of seawater inside the Atoll is markedly smaller than that of surrounding oligotrophic SCS seawaters (Lai et al, 2014). Any substance carried in the outflows from the Atoll could be quickly diluted.…”
Section: Discussionmentioning
confidence: 98%
“…However, according to investigations carried out in the 1980s (Currie and Kalff, ), in oligotrophic environments, bacteria could function as nutrient assimilators and compete with phytoplankton for limiting inorganic nutrients (Azam, ; Kirchman, ; Thingstad et al ., and citations therein). Therefore, the availability of inorganic nutrients might eventually affect bacterial activity and, ultimately the dynamics (accumulation vs. depletion) of dissolved organic carbon (DOC; Thingstad et al ., ; Lai et al ., and citations therein), which has an inventory equal to that of CO 2 in the atmosphere (Benner et al ., ; Hedges, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cheng and Chi [38] and Aparicio et al [39] also stated that eutrophication process will cause an increase in DOC concentration. Lai et al [40] found that bacterial production, primary production and DOC were positively inter-correlated when the inorganic nutrient supplies were potentially abundant. Therefore, correlation analysis was carried out to determine the interaction between DOC and Trophic State Index (TSI) trends in the water surface layer of Fei-Tsui Reservoir.…”
Section: Effect Of Re-oligotrophication In the Fei-tsui Reservoirmentioning
confidence: 99%